PELATIHAN MANAJEMEN BISNIS SYARIAH DALAM BUDIDAYA UDANG HIAS DI DESA GUNUNG BUNDER I, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Muhamad Rizal Gunawan; Ujang Buchori Muslim; Hasbi Ash Shiddieqy (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract Ornamental shrimp do one of the potential to be developed, one of which is conservation efforts are being made to increase production by optimizing it in the enlargement phase, this training activity is held which aims to increase the capacity of youth in ornamental shrimp cultivation and also to increase financial youth in Pamijahan, specifically in Gunung Bunder Village, this training is also assistance to youth through several stages, namely color treatment, enlargement, proper feed and output to the market. This activity is one of the youth services carried out by youth organizations in Pamijahan District. and students of the Sahid Islamic Institute of Bogor. Keywords: ornamental shrimp cultivation, ornamental shrimp market, youth economy.